2022
DOI: 10.1371/journal.pone.0271726
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to Water, Sanitation and Hygiene (WaSH) practices in Southern Africa: A scoping review

Abstract: A healthy and a dignified life experience requires adequate water, sanitation, and hygiene (WaSH) coverage. However, inadequate WaSH resources remain a significant public health challenge in many communities in Southern Africa. A systematic search of peer-reviewed journal articles from 2010 –May 2022 was undertaken on Medline, PubMed, EbscoHost and Google Scholar from 2010 to May 2022 was searched using combinations of predefined search terms with Boolean operators. Eighteen peer-reviewed articles from Souther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…This study provides evidence of the importance of assessing the interface between socioeconomic position and climate with inequalities and climate change being two of the main barriers in WASH 24 . Our results show that among children in the control group, disparities existed by socioeconomic position and season and that the WASH intervention reduced or even nullified existing disparities.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This study provides evidence of the importance of assessing the interface between socioeconomic position and climate with inequalities and climate change being two of the main barriers in WASH 24 . Our results show that among children in the control group, disparities existed by socioeconomic position and season and that the WASH intervention reduced or even nullified existing disparities.…”
Section: Discussionmentioning
confidence: 85%
“…This shows that implementing WASH that does not generate inequalities would require a tailored approach 29 . Members of our team have previously assessed equity in the WASH Benefits Bangladesh interventions with respect to measures of adherence 30 and others have assessed barriers and inequalities in effective WASH practices in the African setting 24 , 31 . These previous studies have demonstrated improved equity in WASH practices and this present analysis demonstrates that those improvements in equity carry forward to improvements in equity in child diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…One of the key barriers to WASH improvements can be a lack of community engagement which WSPs can support to drive as they can empower communities to act [15,44]. Governance structures of many services in Rwanda, including drinking-water, are based upon a decentralized, community-centered approach [45].…”
Section: Community Engagementmentioning
confidence: 99%
“…Critical barriers to improving WASH (water, sanitation, and hygiene) practices identified included low investment in WASH infrastructure, inadequate knowledge about water-borne diseases, and lack of community involvement [56]. To remove these barriers, government intervention is needed to improve sanitation conditions.…”
Section: Table 1 Management Of Greywatermentioning
confidence: 99%